2015
DOI: 10.3390/molecules20010987
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Biochemical Characterization of Apios Tuber Lectin

Abstract: Apios tuber lectin, named ATL, was isolated from Apios americana Medikus by two chromatography steps, hydrophobic chromatography and anion-exchange chromatography. The minimum concentration required for the hemagglutination activity toward rabbit erythrocytes of ATL was 4 μg/mL. ATL was composed of a homodimer of 28.4 kDa subunits. The amino acid sequence of ATL was similar to those of other legume lectins. The lectin showed moderate stability toward heating and acidic pH, and the binding affinity against seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…In present study lectins of ET shows optimum activity at neutral pH-7 and at the same time it is inactive at extreme acidic and basic pH. Similar activity had been observed in many species like Spatholobus parviflorus (Geethanandan 2010), Volvariella volvacea lectins (Mothong 2009), bioactive lectin from Zizyphus oenoplia (Butle & Patil 2015), calyx lectin of Tridax procumbens (Ramteke et al 2005), Apios tuber lectin (Kenmochi et al 2015) and Jackfruit (Artocarpus integrifolia) lectin (Ahmed & Chatterjee 1987).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In present study lectins of ET shows optimum activity at neutral pH-7 and at the same time it is inactive at extreme acidic and basic pH. Similar activity had been observed in many species like Spatholobus parviflorus (Geethanandan 2010), Volvariella volvacea lectins (Mothong 2009), bioactive lectin from Zizyphus oenoplia (Butle & Patil 2015), calyx lectin of Tridax procumbens (Ramteke et al 2005), Apios tuber lectin (Kenmochi et al 2015) and Jackfruit (Artocarpus integrifolia) lectin (Ahmed & Chatterjee 1987).…”
Section: Discussionsupporting
confidence: 83%
“…Similar results were observed in case of Jackfruit (Artocarpus integrifolia) lectins (Ahmed & Chatterjee 1987) and Apios tuber lectin (Kenmochi et al 2015) in which the activity was lost after 85ºC. Geethanandan (2010) and Pereira et al (2015) mentioned that lectins of Spatholobus parviflorus and Colocasia esculenta respectively, lose their activity after 100ºC.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, immunoregulation by isoflavones, particularly genistein, daidzein, and glycitein, have been reported [ 19 ]. In addition, several studies have reported that the lectin shows immunostimulatory activity [ 20 , 21 , 22 ]. In addition to its immunostimulatory activity, Apios has been reported to exhibit anti-hypertension, sEH inhibitory, anti-cancer, and anti-inflammatory activities [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Food lectins affect intestinal function since they interact with the small intestine epithelial cells [ 126 ] and can remain active for several hours, as they can resist the digestive process. Some of them show tolerance to variables such as elevated temperatures, acid pH, and digestive enzymes [ 19 , 127 , 128 ]. The administration of raw leguminous beans or their lectins to rats can provoke effects ranging from weight loss to death.…”
Section: Plant Lectins Against Small Intestine Cancermentioning
confidence: 99%